Advances in the study of subclinical AKI biomarkers - Zou, Chenchen; Wang, Chentong; Lu, Lin (Frontiers in Physiology, 2022)
Acute kidney injury (AKI) is a prevalent and serious illness in all clinical departments, with a high morbidity and death rate, particularly in intensive care units, where prevention and treatment are crucial. As a result, active prevention, early detection, and timely intervention for acute kidney injury are critical. The current diagnostic criteria for acute kidney injury are an increase in serum creatinine concentration and/or a decrease in urine output, although creatinine and urine output merely reflect changes in kidney function, and AKI suggests injury or damage, but not necessarily dysfunction. The human kidney plays a crucial functional reserve role, and dysfunction is only visible when more than half of the renal mass is impaired. Tubular damage markers can be used to detect AKI before filtration function is lost, and new biomarkers have shown a new subset of AKI patients known as “subclinical AKI.” Furthermore, creatinine and urine volume are only marginally effective for detecting subclinical AKI. As a result, the search for new biomarkers not only identifies deterioration of renal function but also allows for the early detection of structural kidney damage. Several biomarkers have been identified and validated. This study discusses some of the most promising novel biomarkers of AKI, including CysC, NGAL, KIM-1, lL-18, L-FABP, IGFBP7, TIMP-2, Clusterin, and Penkid. We examine their performance in the diagnosis of subclinical AKI, limitations, and future clinical practice directions.